Controle da mosca-dos-chifres e carrapato bovino em propriedades leiteiras no norte de Minas Gerais - Evely Giovanna Leite Costa (2016)
The beef production chain in tropical regions face challenges, as the occurrence of parasites that can interfere in growth, performance, productivity and, in extreme cases, can cause mortalities. Little is know about the control of these parasites in semiarid region. This paper aimed to evaluate the practices of management and the application of insecticides used to control Haematobia irritans the effectiveness of commercial acaricides on the tick Rhipicephalus microplus in dairy herds North of the state of Minas Gerais. The control of the horn flies and cattle tick were evaluated in 62 rural properties located in ten municipalities the region assessed. Semi-structured questionnaires were applied in order to obtain information on the characteristics of the properties, on the knowledge about the epidemiology of the horn flies, and on the practices adopted to the control of those parasites. The sensitivity of the ticks on the six cattle herds with high infestations was evaluated using the technique of biocarrapaticidograma. For efficacy testing in the flock, it was held completely randomized design (CRD) with four replications. The data from reproductive groups of engorged females, as posture index, larval emergence and product efficacy they were submitted to analysis of variance and comparing the average by the Duncan (p<0,05). To Haematobia irritans, the data collected were tabulated in contingency tables, and they were analyzed using the chi-square test, considering a significance of 5%. The months from november to march, representing the rainy season in the region North of the Minas Gerais, represented the epochs of large infestations of animals both horn flies (77,19%) as ticks (56,5%), mainly in animals with a higher percentage of European or mixed-race genetics. The cypermethrin was predominant in most part of the commercial insecticides (43,13%) and acaricides (35,5%) used in the properties to control this ectoparasite, followed by the association of active principle with chlorpyrifos and citronellal. As for the sensitivity analysis of the ticks were evaluated four acaricide amitraz and suppose and showed greater efficacy with 99.8 and 86.1%, respectively. Was found resistance in populations of Rhipicephalus microplus to amitraz principles, deltamethrin or association of cypermethrin and chlorpyrifos citronellal, ranging from herds in northern Minas Gerais. Strategic control and alternative measures should be implemented to minimize and reduce losses caused by these parasites addition to avoid selection of resistant insects and mites on herd.